The domain of computational law - Weidong, Ji (Peking University law journal, 2022)
This article has pinpointed computational law in the grand framework of time and space, and illustrated the various mechanism designs aimed to restrict the arbitrariness of power through the efforts of jurisprudence. And these designs are summarized in two basic ideas as follows: (1) rule-based reasoning and the calculation of concepts, (2) science-based experimentation and the institution of calculus. Following the conception of 'legal mathematics' emerging in the process of modernization, the author analyzes in detail the advent of computational law in response to the era of Information and Communications Technology and different stages of its development, capturing a multifaceted computational law. The author emphasizes the intersecting and complementary relations between the components of computational law - jurimetrics (statistics and predictive model), computerization of legal reasoning (the algorithms of expert systems), legal informatics (big data mining and machine learning), legal network structure (graphs and matrix computation) and artificial intelligence governance (data ethics and algorithmic justice). As a conclusion, the author puts forward the important subject of establishing a meta-algorithm for value ranking and value function.